The Use of Authentic Material in Teaching Vocabulary: An Experimental Study at the First Grade of SMA 1 Batukliang in Academic Year 2015-2016 - Hidayati Hidayati (Muhammadiyah University of Mataram, 2017)
Authentic material a real media and materials as a strategy for student learning in the classroom Vocabulary is a list or a series of words that are used to express the idea, or we teach in the foreign language with word knowledge. This research was aimed to find out the use of authentic material in teaching vocabulary. The population of this study is the first grader of SMAN 1 Batukliang which consist of two classes, and the researcher took two classes as the sample, they were class X.1 consist of 30 students, and class X.3 consist of 30 students, the total number of both classes were 60 students. The data in this study were gathered from the pre-test and post-test which given to the experimental and control group before and after treatment was done. In this research, the researcher computed the data by using the t-test formula. After collecting and calculating the data, the researcher found that the mean score of pre-test and post-test for the experimental group were 58.4 and 72, while for the control group were 53 and 61.8. And in testing the hypothesis, the researcher used the t-test formula. The researcher found that t-test was 68.5 and t-table in significant rank 0.05 (5%) was 1.6716. It proved that t-test was higher than t-table (6.073 > 1.6716). The alternative hypothesis was accepted. It indicates that the authentic use material was effective in teaching vocabulary for the first grader of SMAN 1 Batukliang in academic year 2015/2016.